If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 2x + 4 = 34 Reorder the terms: 4 + X + 2x = 34 Solving 4 + X + 2x = 34 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + X + -4 + 2x = 34 + -4 Reorder the terms: 4 + -4 + X + 2x = 34 + -4 Combine like terms: 4 + -4 = 0 0 + X + 2x = 34 + -4 X + 2x = 34 + -4 Combine like terms: 34 + -4 = 30 X + 2x = 30 Add '-2x' to each side of the equation. X + 2x + -2x = 30 + -2x Combine like terms: 2x + -2x = 0 X + 0 = 30 + -2x X = 30 + -2x Simplifying X = 30 + -2x
| 11c-4c= | | swag=pie | | 12-1/3u=12 | | y=8(8)+4 | | (w-5)/(w-1)=(w+2)/(w-3)+1 | | 2x-5=12-45 | | 16(3x-4)=4(12x+1) | | y=8(8)+7 | | 0.36=x/x | | 10pr+8p-5sr-4s= | | 1+2(3x-4)=3(5-x)-4 | | 2x^2-15x+7/6x^2-3x | | (275)(38/55)(11/25) | | x^2-2x=(7+x) | | (w-3)(w-7)=0 | | 4/17(x)=28 | | -3x+4=-2-2x | | (7r-4)(3r-9)=0 | | yw-4w-7y+28= | | -(5y+2)-(-4y-5)=-3 | | (7-u)(5u-8)=0 | | 3(2x-4)=6-3(x+4) | | 3(2x-4)=6-3(x+4) | | s^2-8s-9=0 | | 10t^2+23t-42=0 | | 3(x^2+1)-5x(x^2+x+1)= | | 9+2r-4=7r+15-3r | | 6x+3=-69 | | 2ab^2*4a^2b= | | (26/9)(15/28)(8/65) | | (n-7)*9=54 | | (n-7)*6=12 |